Value co-destruction between customers and frontline employees: A social system perspective - Kashif, Muhammad; Zarkada, Anna K. (My University, 2015)
Purpose – The incidents of customer abuse of frontline service employees during service encounters are increasing which has led to co-destructruction of value. The service strategists makers are struggling hard to frame a holistic picture of such incidents to be able to reduce the number of misbehaviour incidents but still are unable to achieve success. The purpose of this paper is to incorporate a social system perspective to study in detail customer misbehaviour incidents from the perspective of frontline banking employees and customers. Design/methodology/approach – The data from 33 frontline banking employees and 22 customers, 55 in total was collected by structured interviews. The data collection focused a critical incident technique and for the purpose of analysis, thematic analysis was optioned. Findings – The employees and customers both blame each other to trigger a misbehaviour incident during banking transactions. The results reveal a clear communication gap between employees and customers as none of them understand the problems of the other party. The employees think that customers gain power through such incidents while customers believe employees to be ignorant, wasting the time, and lack complete information. Practical implications – The marketing policy makers need to pay respect and complete organisational support to frontline staff working in high contact service firms to cope with misbehaving customers. Originality/value – The study is pioneer in applying a social system perspective to explore employee and customer experiences of misbehaviour incidents during banking service encounters. Furthermore, the study has been first of its type to explore the phenomenon of misbehaviour from a developing country perspective.
Keywords: Pakistan; Marketing; Banking; S-D logic; Customer misbehaviour; Social system